KREATIVITAS, INOVASI, DAN PRODUKTIVITAS DI ERA MERDEKA BELAJAR MELALUI TRANSPFORMASI E-LEARNING - Ike Dian Puspita Sari; Indrawati Pusparini; Adi Adi (JPM PAMBUDI, 2021)
The development of science and technology increasingly encourages renewal efforts in the use of technological results in the learning process. Media that can support learning include computer media. In the era of pandemic, distance learning is very much needed and recommended to suppress the spread of COVID 19. There are many learning media platforms that can be used during distance learning today. Teachers are required to develop skills in making media or developing learning media because the methods and learning media used by teachers greatly affect the results of the teaching and learning process. Thus, there is a need for training in making online-based learning media that will be used during a pandemic and distance learning.